Pleomorphic xanthoastrocytoma with rapid evolution into anaplastic xanthoastrocytoma. Case report and literature review - Papalini, Pablo; Mezzano, Emilio; Passero, Santiago; Olocco, Ricardo; Papalini, Francisco (Revista Argentina de Neurocirugía, 2025)
Background: pleomorphic xanthoastrocytoma (PXA) is a rare tumor of the CNS, its anaplastic variant (PXA-A) is like PXA in terms of clinical presentation but is more aggressive and has a much poorer prognosis. Five to 20% of patients experience recurrences with malignant transformation.Objectives: to describe a case of a patient with PXA with rapid progression to PXA-A.Case description: a 46-year-old patient with histologically confirmed PXA, with rapid progression and malignant transformation to PXA-A, with unfavorable evolution.Intervention: surgery with subtotal macroscopic resection, then reintervention at the time of recurrence and progression.Conclusion: PXA is a rare tumor that can vary its histological grade toward anaplasia (PXA-A) and even toward a variety of glioblastoma. Given the limited evidence available, there is no clear protocol for specific oncological treatment.
Keywords: Anaplastic; Astrocytoma; Pleomorphic; Xanthoastrocytoma